Aidsmap.com: A Comprehensive HIV/AIDS Information Resource. Issue 4 (2nd October 2017) - Morris, Martin
ABSTRACT: Aidsmap <http://www.aidsmap.com > is a frequently updated, comprehensive source of information on HIV and AIDS and is for people living with AIDS, their families, health care professionals, patients, and members of the public wishing to know more about this field. Strengths of the site include the broad range of information it contains, the constantly updated newsfeeds, online tools to assist people living with HIV and AIDS, and the catalogue of resources in 21 languages in addition to English. Much of the information is categorized by complexity and language to one of four levels, enabling quick identification of target audiences.